2019
DOI: 10.1186/s12864-018-5374-6
|View full text |Cite
|
Sign up to set email alerts
|

The Anaplasma ovis genome reveals a high proportion of pseudogenes

Abstract: BackgroundThe genus Anaplasma is made up of organisms characterized by small genomes that are undergoing reductive evolution. Anaplasma ovis, one of the seven recognized species in this genus, is an understudied pathogen of sheep and other ruminants. This tick-borne agent is thought to induce only mild clinical disease; however, small deficits may add to larger economic impacts due to the wide geographic distribution of this pathogen.ResultsIn this report we present the first complete genome sequence for A. ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…Except for those involved in biotin metabolism, genes distinctively present or absent in A. platys do not seem to encode proteins associated with metabolic pathways. Consequently, the metabolic capacity of A. platys is likely to be similar to that previously discussed for other Anaplasma species [8,9,12], characterized by incomplete pathways for glycolysis and the synthesis of most amino acids. In fact, metabolic reconstruction of the A. platys strain showed that the pathways that appear to be complete are the central pathways of energy metabolism from pyruvate oxidation to the citric acid cycle and oxidative phosphorylation, the non-oxidative phase of the pentose phosphate pathway, as well as biosynthetic pathways for fatty acids, coenzyme A, glutathione, and nitrogenous bases (Table S6).…”
Section: Comparative Analysis Of Protein-coding Genessupporting
confidence: 54%
See 3 more Smart Citations
“…Except for those involved in biotin metabolism, genes distinctively present or absent in A. platys do not seem to encode proteins associated with metabolic pathways. Consequently, the metabolic capacity of A. platys is likely to be similar to that previously discussed for other Anaplasma species [8,9,12], characterized by incomplete pathways for glycolysis and the synthesis of most amino acids. In fact, metabolic reconstruction of the A. platys strain showed that the pathways that appear to be complete are the central pathways of energy metabolism from pyruvate oxidation to the citric acid cycle and oxidative phosphorylation, the non-oxidative phase of the pentose phosphate pathway, as well as biosynthetic pathways for fatty acids, coenzyme A, glutathione, and nitrogenous bases (Table S6).…”
Section: Comparative Analysis Of Protein-coding Genessupporting
confidence: 54%
“…Subunits of these complex are encoded by at least 11 genes (virB1-11), all of which are considered important determinants of virulence in Anaplasmataceae. Expansion of gene families associated with the type IV secretion system is well documented in Anaplasma, with several reported copy number variations across species [12,28,29]. In the A. platys genome, we found duplication or expansion in the genes encoding VirB2, VirB8, VirB9, and VirB10.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A. ovis is an intraerythrocytic rickettsial pathogen that mainly affects domestic sheep and goats, but has also been reported to be present in some wild ruminants and dogs with mild clinical symptoms (Zaid et al, 2019). However, symptoms may be exacerbated by stressors such as co-infection, elevated temperature, and animal movement disorders throughout Asia, Africa, Europe and the United States (Hornok et al, 2011;Cabezas-Cruz et al, 2019;Enkhtaivan et al, 2019;Liu et al, 2019). This pathogen also poses a potential threat to humans (Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%